1999
DOI: 10.4141/a98-070
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding conjugated linoleic acid on subsequent pork quality

Abstract: . 1999. The effects of feeding conjugated linoleic acid on subsequent pork quality. Can. J. Anim. Sci. 79: 45-51. Feeding conjugated linoleic acid (CLA) has recently been shown to repartition fat to lean in pigs. The present study was undertaken to determine if feeding CLA affects pork quality. Pigs were fed a cereal-based diet containing either 2% CLA or 2% sunflower oil. Fifty-four pigs (27 gilts and 27 barrows) were fed per diet, and diets were fed from 61.5 to 106 kg liveweight. Diet did not affect postmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
58
2
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 23 publications
14
58
2
6
Order By: Relevance
“…일반적으로 식육의 보수력은 pH와 밀접한 관련이 있으며 (Cresopo et al, 1978), 육제품에 첨가된 소금 에 의해 육의 보수력과 pH를 상승시킨다고 하였다 (Barbut et al, 1988;Kim and Kim, 1999 육색은 육색소인 myoglobin이 산소를 함유하고 있음에 따 라 변하며, 육조직 내의 효소 활동, 저장 온도, 미생물 오염 도 및 pH 등에 따라 변화된다고 하였다 (Dugan et al, 1999). 육색은 외관 평가에 있어서 매우 중요한 항목이며, 황색이 증가할수록 입맛을 돋게 하여 기호성에 좋은 영향을 준다고 (Candogan andKolsarici, 2003: Chang andCarpenter, 1997), 소시지의 지방 함 량이 적을수록 조직감이 감소한다고 하였다 (Andres, 2006 …”
unclassified
“…일반적으로 식육의 보수력은 pH와 밀접한 관련이 있으며 (Cresopo et al, 1978), 육제품에 첨가된 소금 에 의해 육의 보수력과 pH를 상승시킨다고 하였다 (Barbut et al, 1988;Kim and Kim, 1999 육색은 육색소인 myoglobin이 산소를 함유하고 있음에 따 라 변하며, 육조직 내의 효소 활동, 저장 온도, 미생물 오염 도 및 pH 등에 따라 변화된다고 하였다 (Dugan et al, 1999). 육색은 외관 평가에 있어서 매우 중요한 항목이며, 황색이 증가할수록 입맛을 돋게 하여 기호성에 좋은 영향을 준다고 (Candogan andKolsarici, 2003: Chang andCarpenter, 1997), 소시지의 지방 함 량이 적을수록 조직감이 감소한다고 하였다 (Andres, 2006 …”
unclassified
“…Other authors also found that pork tenderness did not differ for chops from pigs supplemented with CLA (Dugan et al 1999;Thiel-Cooper et al 1999) or chromium (Page et al 1992;Boleman et al 1995).…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, the addition of MTO to the combination of CrNic and L-carnitine was not beneficial to visual color. Additionally, Dugan et al (1999) and Eggert et al (1999) observed that CLA did not affect visual color of the LM, whereas Thiel-Cooper et al (1999) and Larsen et al (1999) found that a* values were increased with CLA supplementation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…effect on tissue fat accretion in mice (Park et al 1997(Park et al , 1999 and swine (Dugan et al 1997(Dugan et al , 1999Ostrowska et al 1999) and to reduce the yield of milk fat (Loor and Herbein 1998;Giesy et al 1999) in dairy cattle. However, the relationship between feeding CLA and fat reduction in humans has yet to be clearly established (Atkinson 1999;Blankson et al 2000;Kelly 2001).…”
mentioning
confidence: 99%